Analysis on the requirements of future data network - Xiuli ZHENG; Jiayao TAN; Sheng JIANG; Chuang WANG (Dianxin kexue)
Internet is the hub of information exchange.The innovation of network technology is the basis and enabler for innovation of new applications and business.The design of the future internet is expected to base on assumptions and visions for a future intelligent society.The new requirements of data networks for novel forward-looking applications in the future were firstly introduced,then the technological gaps of current data networks were analyzed,and new capabilities of data networks in the next 8~10 years were finally defined,aiming to provide guidance for the design of future data networks.